Prevalence and characteristics of cervical human papillomavirus genotypes and cervical lesions among 58630 women from Guangzhou, China - Jiang Huiyun; Ding Jie; Wang Huan; Yang Yuebo; Li Xiaomao (Elsevier, 2023)
Background: To assess the prevalence and characteristics of human papillomavirus (HPV) genotypes and its associated cervical lesions in Guangzhou, China, which may be useful for adjusting area-specific cervical cancer prevention and control strategies. Methods: A total of 58630 women were enrolled. Cervical specimens were collected for HPV DNA testing and/or cervical cytology. Patients with visible cervical lesions or abnormal screening results underwent further cervical biopsies. Result: The overall HPV positive rate was 14.07%. The top five genotypes in Guangzhou were HPV 52 (3.06%), HPV 16 (2.28%), HPV 58 (1.80%), HPV 51 (1.32%), and HPV 39 (1.15%). The prevalence of overall HPV and vaccine-targeted HPV genotypes showed a significantly decreasing trend from 2016 to 2019 (P < 0.05). While, the infection rate of HPV 35 increased significantly during this time (P = 0.015). The age-specific prevalence of any HPV genotypes showed a bimodal curve, which peaked firstly among the < 20 y age group, and then peaked secondly among the > 59 y age group. Among HPV-positive women, the proportions of HSIL and cervical cancer increased significantly with age (P < 0.05). Among > 59 y age group, 9.35% HPV-positive cases were diagnosed as cervical cancer. HPV 16/18 was the most common cause of cervical cancer. While, the percentage of non-HPV 16/18 infection among cervical cancer patients increased over time, from 15.21% in 2015 to 26.32% in 2019 (P = 0.010). Besides that, the prevalence of non-HPV 16/18 genotypes among cervical cancer patients significantly increased with age, which peaked at the > 59 y age group (P = 0.014). Conclusion: Although the prevalence of any HPV and vaccine-targeted HPV genotypes decreased significantly with time, it is still important to follow the HPV genotypes and their associated cancer risk after the large-scale popularization of HPV vaccine. And age should be taken into consideration in screening strategies and risk-based management of cervical cancer in Guangzhou.